TEETH AVULSION SECONDARY TO ORO-TRACHEAL INTUBATION IN A TERTIARY HEALTHCARE FACILITY. A CASE SERIES - Adedapo Afolabi; Enoch Idowu; G Elekwachi; OT Dada; MD Adesunloro; BS Araoye (Nigerian Dental Association, 2023)
General anaesthesia using endo-tracheal intubation carried out to provide pain free surgical and medical procedures sometimes results in Traumatic Dental Injuries [TDIs]. Among the rarely reported TDI complication is Tooth avulsion. We present 2 cases of such complications, factors which can be responsible, management of such cases and the need to educate medical and paramedical personnel of what to do if such complication arises before definitive management can be carried out by the Dentist. Such awareness will go a long way in preventing unnecessary litigations which might likely occur from such routine procedures.